1998
DOI: 10.1046/j.1365-2567.1998.00567.x
|View full text |Cite
|
Sign up to set email alerts
|

Rat NKR‐P1+ CD3+ T cells: selective proliferation in interleukin‐2, diverse T‐cell‐receptor‐Vβ repertoire and polarized interferon‐γ expression

Abstract: Cells expressing markers of both natural killer and T lymphocytes (NK T cells) in humans and mice express a restricted T-cell receptor (TCR) repertoire, are of CD4- CD8- or CD4+ CD8- phenotype, and upon anti-CD3 stimulation secrete large amounts of interleukin-4 (IL-4) and interferon-gamma (IFN-gamma). NK T cells may be the primary source of IL-4-promoting T helper type 2 (Th2) responses and/or they might be involved in regulating the balance between Th1- and Th2-type immune responses, and may consequently aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 41 publications
(56 reference statements)
0
9
0
Order By: Relevance
“…As previously described (1,6,28), ϳ30% of mouse IHL coexpressed NK1.1 and TCR and were either CD4 ϩ or CD4 Ϫ CD8 Ϫ , whereas rat IHL comprised rather low numbers of NKR-P1A (rat homolog of NK1.1) and TCR ϩ cells, most of them being CD8␣␤ ϩ . Our attempts to directly detect rat iNKT cells by staining with ␣-GalCer-loaded mouse CD1d tetramers failed, although the capacity of rat IHL to produce IFN-␥ and IL-4 production after stimulation with ␣-GalCer suggested that there is indeed a functional iNKT cell population in F344/Crl rats.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…As previously described (1,6,28), ϳ30% of mouse IHL coexpressed NK1.1 and TCR and were either CD4 ϩ or CD4 Ϫ CD8 Ϫ , whereas rat IHL comprised rather low numbers of NKR-P1A (rat homolog of NK1.1) and TCR ϩ cells, most of them being CD8␣␤ ϩ . Our attempts to directly detect rat iNKT cells by staining with ␣-GalCer-loaded mouse CD1d tetramers failed, although the capacity of rat IHL to produce IFN-␥ and IL-4 production after stimulation with ␣-GalCer suggested that there is indeed a functional iNKT cell population in F344/Crl rats.…”
Section: Discussionmentioning
confidence: 55%
“…This is in stark contrast to the mouse, in which most of the NK1.1-positive T cells, and nearly all iNKT cells, are CD4 ϩ or CD4 Ϫ CD8 Ϫ . Secondly, NKR-P1A-positive rat T cells produce IFN-␥ but not IL-4 upon in vitro CD3 stimulation (28). Thus, it appears that these cells are not the equivalent of mouse iNKT cells.…”
Section: T He Hallmark Of Invariant Nkt Cells (Inkt Cells)mentioning
confidence: 94%
See 1 more Smart Citation
“…The function of NKT cells in the immune system appears strongly related to their IFN-␥ secretion and cytotoxic properties (22)(23)(24)(27)(28)(29)(30). Our results clearly showed that peripheral NKT cells of NOD mice carry a pronounced defect in their TCR-mediated-and IL-12-induced activation and IFN-␥ secretion.…”
Section: Discussionmentioning
confidence: 56%
“…Furthermore, former attempts to identify rat iNKT cells using surrogate markers have also failed as no cell population has yet been found with the features predicted for iNKT cells based on their mouse counterparts. Instead, rat NKR-P1A/B-positive T cells are found in the spleen and the liver at similar frequencies, show no BV8S2 or BV8S4 bias, produce IFN-γ but not IL-4, and most of them express CD8β [9,12,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%